Anti-inflammatory and biologic drugs for atopic dermatitis: a therapeutic approach in children and adolescents - Caffarelli, Carlo; Giannetti, Arianna; Giannì, Giuliana; Ricci, Giampaolo (Frontiers in Medicine, 2023)
Atopic dermatitis is chronic inflammatory disorder with heterogeneous pathogenesis correlated with a dysregulation of the immune system with a prevalence of T2-mediated immune pathway. Recent understanding AD pathogenesis has allowed to develop new drugs targeting different mechanisms and cytokines that have changed the treatment approach. The aim of this review is to update knowledge on standard treatment and on recent advancements for the control of skin inflammation. In the light of recent guidelines, we report the clinical efficacy of novel treatments with a particular attention on those situations where biologics and small molecules are involved.